Evaluating of quality of rice bran protein concentrate prepared by a combination of isoelectronic precipitation and electrolyzed water treatment. (January 2019) - Watanabe, Masanori; Yamada, Chikako; Maeda, Isamu; Techapun, Charin; Kuntiya, Ampin; Leksawasdi, Noppol; Seesuriyachan, Phisit; Chaiyaso, Thanongsak; Takenaka, Shinji; Shiono, Tadahiko; Nakamura, Kozo; Endo, Shujiro
Abstract: A combination of isoelectronic precipitation and electrolyzed water treatment (IP-EWT) process was use for simultaneous recovery of protein and phosphorus compounds from heat-stabilized defatted rice bran (HSDFRB). The highest protein content (65.1 w/w%) recovery ratio (over 50%) of protein concentrate were attained by two-stage protein extraction with IP-EWT. Analysis of amino-acid composition demonstrated excellent amino acid value (76.6%) in the protein fraction than those of commercial cereals such as rice (61%), wheat (39%), and corn (31%). In addition, according to SDS-PAGE and immunoblotting analysis, neither rice allergenic protein nor heavy metals were detected in either HSDFRB or protein fractions extracted by IP-EWT. These results suggest that as an eco-friendly process, this combined (IP-EWT) process is suitable for practical recovery of highly concentrated and safe protein from HSDFRB without using enzymes or chemicals such as organic solvents, buffering agents, and surfactants. Highlights: Rice protein concentrate was recovered and purified by using IP-EWT process. Excellent amino acid value (76.6%) was indicated in the protein fraction. Allergenic protein were not detected in HSDFRB and protein fractions. IP-EWT process is suitable for recovery of highly concentrated and safe rice protein.